Estimation of acoustic indices with CVs for Northeast Arctic saithe in the Norwegian coastal survey 2003-2017 applying the Sea2Data StoX software - Mehl, Sigbjørn; Johnsen, Espen; Skålevik, Åsmund; Aglen, Asgeir (Havforskningsinstituttet, 2018)
Source at http://hdl.handle.net/11250/2562514 The Sea2Data software StoX was applied to estimate acoustic indices with CVs and length and weight at age for Northeast Arctic saithe from the Norwegian coastal survey Varanger - Stad in 2013 to 2017. The indices are compared to indices previously estimated by the BEAM software, and differences are mainly explained by different strata areas. Sea2Data programmet StoX er brukt til å estimere akustiske indekser med CV og lengde og vekt ved alder for nordøstarktisk sei fra det norske kysttoktet Varanger – Stad i 2013 til 2017. Indeksene er sammenlignet med indekser tidligere estimert med programmet BEAM, og forskjeller er i hovedsak forklart ved forskjeller i strata-areal.